A comparative study on the whitening effectivity and safety of over-the-counter and dentist prescribed tooth whitening products - Chan Jr., Eduardo; Rasa, Helena Mae.; Galban, Angelita (Adviser).
With the changing inclination of the public towards esthetics, a growing number of people seek more than just healthy and clean teeth - they want whiter teeth to further enhance their physical appearance. Because of this demand, aside from the regular dental clinic that offer tooth whitening as part of their treatments, special clinics that solely cater to patients who want their teeth whitened have opened. Meanwhile, Colgate-Palmolive Philippines formally introduced Colgate Simply White Clear Whitening Gel, an over-the-counter whitening product, to the Philippine market on June of 2003. This gave the public a more economical alternative to in-office and dentist-supervised at-home bleaching. After more than a decade of research and clinical use, the whitening effectiveness and safety of dentist-prescribed tooth whitening products have been established (Li 2000). On the other hand, due to the unmonitored nature of the over-the-counter whitening effects, much less is known with the whitening effectiveness and safety of use of thoi-o products Bscsus© of this an in vivc exoerimsn^a! single-blind clinic?*! trial that aimed to compare the whitening effectivity and safety of over-the-counter and dentist prescribed tooth whitening products was done. The results obtained from the study showed that there is a difference in whitening effectivity of over-the-counter and dentist prescribed tooth whitening products, but no difference exists in terms of their safety use of.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Teeth -- Bleaching; Dentistry -- Aesthetic aspects